What Role Can Avatars Play in e-Mental Health Interventions? Exploring New Models of Client–Therapist Interaction - Rehm, Imogen C.; Foenander, Emily; Wallace, Klaire; Abbott, Jo-Anne M.; Kyrios, Michael; Thomas, Neil (Frontiers in Psychiatry, 2016)
In the burgeoning field of e-mental health interventions, avatars are increasingly being utilized to facilitate online communication between clients and therapists, and amongst peers. Avatars are digital self-representations which enable individuals to interact with each other in computer-based virtual environments. In this narrative review, we examine the psychotherapeutic applications of avatars that have been investigated and trialed to date. Five key applications were identified: (1) in the formation of online peer support communities; (2) replicating traditional modes of psychotherapy by using avatars as a vehicle to communicate within a wholly virtual environment; (3) using avatar technology to facilitate or augment face-to-face treatment; (4) as part of serious games, and (5) communication with an autonomous virtual therapist. Across these applications, avatars appeared to serve several functions conducive to treatment engagement: (1) facilitating the development of a virtual therapeutic alliance; (2) reducing communication barriers; (3) promoting treatment-seeking through anonymity; (4) promoting expression and exploration of client identity, and (5) enabling therapists to control and manipulate treatment stimuli. Further research into the feasibility and ethical implementation of avatar-based psychotherapies is required.